Investigation of flow in elbow pipe using lattice Boltzmann method - Nik Muqaffi, Nik Jaffar (2009)
The investigation is about the flow in elbow pipe with the different Reynold numbers and geometry mesh. There are three types of elbow pipe geometry in this case study which known as elbow pipe with expansion ratio 1.0, 1.5 and 2.0. All types of elbow pipe that has been applied with laminar flow that Reynold number 100, 150, 200 and 250. The simulation of the model was studied under isothermal lattice Boltzmann method condition in which we investigated computationally in a two-dimensional configuration using a fluid dynamics program. The different Reynold numbers and expansion ratio has given the different flow pattern around the elbow pipe region. The minimum Reynold numbers has been increased after the flow pattern in elbow pipe was simulate and elbow pipe with expansion ratio 2.0 has given the maximum reattachment length of the circulation that occur in elbow pipe. Finally, for future investigation the correlations obtained from this numerical result could be used to investigate the flow in the elbow pipe.